Ad maiorem Dei gloriam. Numeracy levels in the Guarani Jesuit missions - Èric Gómez-i-Aznar (European Historical Economics Society (EHES), 2020)
This work provides data on human capital for the Guarani Jesuit missions during the 18th century. Based on the age heaping methodology, the results of a large sample (over 3,600 observations) suggest that the knowledge of numerical skills in these missions was exceptional. A comparison with other regions and locations with different institutional frameworks, religious or otherwise, or led by other religious orders, confirms the exceptionality of the Guarani Jesuit missions. The model of these missions, based on productive self-sufficiency and egalitarian and cohesive social organization, as well as respect for the pre-existing culture exemplified by their Guaraníization and adaptation to the Guarani world view and language, could explain their successful educational performance and the intergenerational transmission of human capital beyond the disappearance of the Jesuit missions after 1767.
Keywords: I21; I25; J24; O4; 330; Human Capital; Economic Development; Numeracy; Institutions